ANALISIS FAKTOR-FAKTOR PENENTU HARGA RUMAH DI INDONESIA: PENDEKATAN HARGA HEDONIK - , Mayla Safuro Lestari Putri; , Dr.Tri Widodo, M.Ec.Dev. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The house is a basic life needs that must be met. In the social dimension, house is seen as a refuge. While the legal dimension, house ownership is seen as a property right that ownership has an impact on institution building, and from the economic dimension, house is a source of prosperity, investment and economic value. Housing needs as part of residential property increased as well as increase in population and the fulfillment of basic needs. In the property market, house price is quite important because it reflects the inherent attributes in it. Thus, it becomes important to analyze the factors that affect house price. This study will be helpful in the determination or evaluation of housing policy for the government in terms of the settlement. This study uses Indonesian Family Life Survey (IFLS) data in 2007. Hedonic price approach to the method of Ordinary Least Square (OLS) used as a basis for analyzing how much influence the attributes of a house on housing prices. Regression results indicate that structural characteristics (variable rate of house, spacious of house, the amount of space, and type of floors (ceramic/marble/granite)